DOI: 10.31274/etd-180810-4777
|View full text |Cite
|
Sign up to set email alerts
|

Website gender perceptions: effects and recommendations for gender inclusivity

Abstract: I would like to dedicate this thesis to four wonderful groups of people. First, to Deidra and Andrew-you always made sure to listen when I lectured on "the plight". Your interest in my work is worth more to me than I could ever show. Second, to the driven and talented women in science, engineering, and the artsyou gave me the courage to flourish. Third, to my mother and father for having patience with me when they probably shouldn't havethank you. Finally, to every reader who makes it to the end of this docume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…In a series of studies, design elements and their impact on perceptions of a website's gender, professionalism, and user experience were studied. In a follow-up study, the perceived gender of the websites was shown to affect assessment of websites' professionalism, workload, usability, likability and visual appeal (Stonewall, 2016). In the area of evaluation, we have been studying the effect of bias in student peer assessment in team-centric classroom strategies such as Team-Based Learning.…”
Section: Research In User Centered Design To Address the Interaction Of Technology And Biasmentioning
confidence: 99%
“…In a series of studies, design elements and their impact on perceptions of a website's gender, professionalism, and user experience were studied. In a follow-up study, the perceived gender of the websites was shown to affect assessment of websites' professionalism, workload, usability, likability and visual appeal (Stonewall, 2016). In the area of evaluation, we have been studying the effect of bias in student peer assessment in team-centric classroom strategies such as Team-Based Learning.…”
Section: Research In User Centered Design To Address the Interaction Of Technology And Biasmentioning
confidence: 99%